Radiotherapy in the management of carcinoma of the vulva in HIV positive and negative patients : an institutional experience - Opakas, Jesse Elungat (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2015.